Probing the case for manufacturer liability for harms caused by judgment-proof consumers to others - Tim Friehe; Christoph Rössler; Elisabeth Schulte (European Journal of Law and Economics, 2023)
We study whether it is socially desirable to hold a monopolistic firm liable for the harm its potentially judgment-proof consumers inflict on third parties. Consumers' judgment-proofness limits potential product differentiation by pooling different consumer types with uniform liability exposure. The firm's safety choices are distorted in both regimes under consideration: consumer-only liability and residual-manufacturer liability. We find that residual-manufacturer liability dominates consumer-only liability if the monopolistic firm can observe consumers' types, or if consumers' types are not observable but heterogeneity stems only from their asset levels. However, if the monopolistic firm cannot observe consumers' types and heterogeneity stems from their harm levels, it is more difficult to make a case for residual-manufacturer liability.
Keywords: K13; L12; 340; Liability; Judgment proofness; Safety; Precaution; Consumer